Patient centered infertility care: The health care provider’s perspective - Alana Streisfield (The Beryl Institute, 2015)
This study describes what health care providers (HCPs) of fertility services perceive their patients to value most, as well as HCPs’ self-evaluation in provision of patient centered infertility care (PCIC). The Patient Centeredness Questionnaire Infertility (PCQ-I) was administered to all clinic staff and completed by approximately 60%. Mean scores and standard deviations were calculated for each dimension as well as for the global score. HCPs ranked staff communication as the highest of the dimensions and accessibility of care as the lowest, respectively indicating areas of strength and weakness. Degree of variance within scoring was used as a marker of consistency of assessment. Ranking of staff competence was the most uniform and ranking of accessibility the most varied, suggesting HCPs are confident in assessing patients’ perceptions of competence, but not with respect to accessibility. Staff communication was thought to be the most important dimension of PCIC for patients, based on the correlation with global score, while care organization was thought to be the least important, showing the lowest correlation with the global satisfaction score. This is the first study to describe North American HCPs’ perceptions of PCIC. This information will inform further professional development in provision of quality PCIC.